APPARATUS FOR INDUCTION HARDENING - FITCH STEPHEN B; MILLS JERRY; STUEHR WILLIAM; GADUS JOHN; JOHNSON STEPHEN P (2015)
An apparatus for magnetic induction hardening of a workpiece includes a magnetic tool having a body portion formed of a generally non-magnetic material. The body portion has a surface configured to be positioned in close proximity to the workpiece being hardened. The apparatus further includes a magnetic arrangement coupled to the body portion at or adjacent the surface of the body portion and configured to provide regions of alternating polarity. A workpiece holder is configured to support the workpiece in close proximity to the surface of the magnetic tool. A drive arrangement for rotating the magnetic tool relative to the workpiece holder about an axis of rotation is provided to induce heating of the workpiece to achieve a temperature in the austenitic range of the workpiece resulting in hardening of the workpiece through a microstructural transformation.